Finite‐time stability of non‐linear systems with impulsive effects due to logic choice. Issue 11 (1st July 2018) - Zhang, Junhui; Sun, Jitao; Wang, Qing‐Guo
Abstract : This study is concerned with the finite‐time stability of non‐linear systems with impulsive effects due to logic choice. Firstly, we introduce a class of non‐linear systems with logic‐induced impulses and it generalises the model established in Suo and Sun (2015). Then, based on semi‐tensor product technique, several criteria for finite‐time stability for the system are given. Finally, two numerical examples are provided to illustrate authors' results.